Gut Microbiota and Gestational Diabetes Mellitus: A Review of Host-Gut Microbiota Interactions and Their Therapeutic Potential - Hasain, Zubaidah; Mokhtar, Norfilza Mohd; Kamaruddin, Nor Azmi; Mohamed Ismail, Nor Azlin; Razalli, Nurul Huda; Gnanou, Justin Vijay; Raja Ali, Raja Affendi (Frontiers in Cellular and Infection Microbiology, 2020)
Gestational diabetes mellitus (GDM) is defined as impaired glucose tolerance recognized during pregnancy. GDM is associated with metabolic disorder phenotypes, such as obesity, low-grade inflammation, and insulin resistance. Following delivery, nearly half of the women with a history of GDM have persistent postpartum glucose intolerance and an increased risk of developing type 2 diabetes mellitus (T2DM), as much as 7-fold. The alarming upward trend may worsen the socioeconomic burden worldwide. Accumulating evidence strongly associates gut microbiota dysbiosis in women with GDM, similar to the T2DM profile. Several metagenomics studies have shown gut microbiota, such as Ruminococcaceae, Parabacteroides distasonis, and Prevotella, were enriched in women with GDM. These microbiota populations are associated with metabolic pathways for carbohydrate metabolism and insulin signaling, suggesting a potential “gut microbiota signature” in women with GDM. Furthermore, elevated expression of serum zonulin, a marker of gut epithelial permeability, during early pregnancy in women with GDM indicates a possible link between gut microbiota and GDM. Nevertheless, few studies have revealed discrepant results, and the interplay between gut microbiota dysbiosis and host metabolism in women with GDM is yet to be elucidated. Lifestyle modification and pharmacological treatment with metformin showed evidence of modulation of gut microbiota and proved to be beneficial to maintain glucose homeostasis in T2DM. Nonetheless, post-GDM women have poor compliance towards lifestyle modification after delivery, and metformin treatment remains controversial as a T2DM preventive strategy. We hypothesized modulation of the composition of gut microbiota with probiotics supplementation may reverse postpartum glucose intolerance in post-GDM women. In this review, we addressed gut microbiota dysbiosis and the possible mechanistic links between the host and gut microbiota in women with GDM. Furthermore, this review highlights the potential therapeutic use of probiotics in post-GDM women as a T2DM preventive strategy.